What drives a salesperson's goal achievement? An empirical examination. Issue 1 (5th February 2018) - Kumar, V.; Goreczny, Ashley; Maurer, Todd
Abstract : Purpose: The purpose of this study is to understand how a salesperson's preset goals, customer satisfaction levels and past performance affect the extent of goal achievement, as well as how job-specific attitudes and emotions affect the relationship between preset goals and goal achievement. Design/methodology/approach: This study uses a modeling framework with both main, moderating and mediating effects, using transaction data and survey results from a telecommunications firm. Findings: The results indicate that preset goals and customer satisfaction, interestingly, have an inverted-U relationships with goal achievement. Further, attitudes and emotions regarding workplace conduciveness and workplace ethics and diversity, reduce the effect preset goals have on goal achievement. However, attitudes and emotions regarding workplace philosophy strengthens the effect preset goals have on goal achievement, whereas with disagreement, this relationship diminishes. Research limitations/implications: Two of the primary limitations of this study are: one, because of the cross-sectional nature of the study, there is limited opportunity to control for unobserved heterogeneity; and two, performance goal achievement, though is important for the firm, is one of many potential goals that affect a salesperson. For example, customer satisfaction goals or a one-time special event goals could play a role. Therefore, only using performance goal achievement could be a limitation of this study. Originality/value: This study contributes to academic literature in three ways. First, it demonstrates the diminishing effect of customer satisfaction on goal achievement. Second, it identifies an inverse U-shaped relationship between preset goals and goal achievement. Finally, it examines how attitudes and emotions regarding workplace culture (conduciveness, ethics and diversity and philosophy) affect the relationship between preset goals and goal achievement.